PENERAPAN MANAJEMEN ENERGI DI HOTEL SEBAGAI USAHA MENGURANGI EMISI KARBON - I.A. Dwi Giriantari; Made Sumantera (Environmental Research Center (PPLH) of Udayana University, 2009)
Energy management is very crucial now days due to the energy crisis and considering the emission produce by the activity. The production of energy releases large amount carbon emission to the environment, in addition the energy usage also produces carbon emission. Therefore, the unwise usage of energy leads to damage environment due to double amount of carbon emission. Application an energy management has an important role in reducing energy use in hotel particularly. Energy management in a hotel has produced a decision to apply a heat recovery system at their air condition system. It has significantly reduced oil consumption of the boiler from 772.274 litre/year to 158.472 litre/year that means a reduced on the carbon emission of 1.641.307 kg /year.